The Influence of Work Environment and Workload on Productivity Employees with Social Support as A Moderating Variable - Muhammad Reza Hamzah Fansury; Munjiati Munawaroh (Lembaga Bale Literasi, 2026)
The food and beverage industry in Yogyakarta is dominated by small and medium enterprises (SMEs) that possess high potential but struggle with improving employee productivity. This study aims to analyze the influence of the work environment and workload on employee productivity, and examine the moderating role of social support in the relationship between workload and productivity. The research was conducted from December 2024 to February 2025 involving 214 respondents selected based on specific criteria. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 4.1.0.9. The results show that the work environment does not significantly affect employee productivity. However, workload has a positive and significant effect on productivity. Meanwhile, social support does not moderate the relationship between workload and productivity. Productivity in Yogyakarta’s food and beverage SMEs is mainly influenced by workload, not the work environment or social support, highlighting the need for balanced workload management and structured recovery strategies.